Sensitivity and uncertainty analysis of PnET-BGC to inform the development of Total Maximum Daily Loads (TMDLs) of acidity in the Great Smoky Mountains National Park. (September 2017) - Fakhraei, Habibollah; Driscoll, Charles T.; Kulp, Matt A.; Renfro, James R.; Blett, Tamara F.; Brewer, Patricia F.; Schwartz, John S.
Abstract: The biogeochemical model, PnET-BGC, has been used to evaluate the long-term acid-base response of surface waters to changes in atmospheric acid deposition. We propose a methodology to identify the input factors of greatest model sensitivity and propagate uncertainty of input factors to model outputs. The quantified model uncertainty enabled application of an "exceedance probability" approach to determine allowable atmospheric deposition in the form of Total Maximum Daily Loads (TMDLs) for twelve acid-impaired streams in Great Smoky Mountains National Park. Results indicate that acidification of surface water resulting from acidic deposition has been substantial. Even if current atmospheric deposition is reduced to pre-industrial levels, only one of the twelve impaired streams might be recovered to its site-specific standard by 2050. Our sensitivity analysis indicates that the model is most sensitive to precipitation quantity, air temperature and calcium weathering rate, and suggests further research to improve characterization of these inputs. Highlights: We reviewed the literature on sensitivity and uncertainty analysis. We provided R scripts for sensitivity and uncertainty analysis of multivariable models. We developed TMDLs of acidity for streams in the Great Smoky Mountain National Park (GRSM). A limited number of acid-impaired streams in the GRSM can be recovered in a few decades. Recovery of ecosystems from acid deposition is a slow process in the GRSM and takes more than a century to achieve.